2014
DOI: 10.1177/0009922814533186
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Pharmacogenomic Testing in Pediatric Practice

Abstract: Clinicians and patients continue to convey interest in personalized medicine. The objective of personalized medicine is to improve healthcare by tailoring disease prevention, diagnosis, and treatment strategies for individuals based on their unique clinical history and genetic composition. This article offers an overview of pharmacogenomics, discusses caveats specific to pharmacogenomics in pediatric populations, provides evidence-based recommendations for pediatric clinicians, and offers insight regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…While at this time no studies have found genetic polymorphisms that have clinical associations with response to MTX among IBD patients, there is some evidence that genetic polymorphisms may play a role in general disease response. 22,23 Furthermore, certain metabolism pathways involved may have different rates among children and adults. 23 The lower long-term clinical remission rate in this meta-analysis may be explained by the fact that the rates described here are from all patients reported who were included in the cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While at this time no studies have found genetic polymorphisms that have clinical associations with response to MTX among IBD patients, there is some evidence that genetic polymorphisms may play a role in general disease response. 22,23 Furthermore, certain metabolism pathways involved may have different rates among children and adults. 23 The lower long-term clinical remission rate in this meta-analysis may be explained by the fact that the rates described here are from all patients reported who were included in the cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore, certain metabolism pathways involved may have different rates among children and adults. 23 The lower long-term clinical remission rate in this meta-analysis may be explained by the fact that the rates described here are from all patients reported who were included in the cohort studies. The maintenance phase in this analysis was defined as administration of MTX for the duration of 1 year, as some cohort studies did not report short-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…These new regulations allowed the FDA to require that drug manufacturers conduct clinical trials that included a significant number of patients. They also provided some incentives for companies to pursue development of pediatric formulations of both new and older off-patent drugs (Korbel et al 2014).…”
Section: Lack Of Evidence In Pediatric Pharmacotherapymentioning
confidence: 99%
“…The Food and Drug Administration (FDA) recommends genetic testing for the enzyme TPMT before initiating mercaptopurine (6-MP) therapy. Clinicians should consider lower doses of 6-MP in their patients who are carriers of a variant TPMT allele and should consider treatments other than 6-MP for ALL patients that are homozygous for the TPMT variant allele (Korbel et al 2014). As 6-MP is used in pediatrics for the treatment of acute lymphoblastic leukemia (ALL) and inflammatory bowel disease, it is vital to test TPMT levels to ensure optimal dosing of 6-MP (Kirschner 1998;Schmiegelow et al 2014).…”
Section: Pharmacogenomic Testing In Pediatric Practicementioning
confidence: 99%
“…Therefore, pharmacogenomic clinical testing, as an approach could help guide the choice of medication within and between classes of drugs where therapeutic alternatives exist and the selection of an initial dose, is especially important in pediatric practice. However, implementation of pharmacogenomic testing in pediatric care is still scarce [21], this may partly because many pharmacogenomics knowledge come from researches of adults and cannot extrapolated directly to children patients [21,22], and also because it is unclear to what extent drug inefficacy and adverse events could be mitigated by implementing pharmacogenomic testing in pediatric patients.…”
mentioning
confidence: 99%